Application of GIS Tools to analyze changes in road network parameters: The case of Berkane province - Aouni Youssef; El Moudni El Alam Souad; Toumi Abdennaby (E3S Web of Conferences)
Road network management is an aspect of infrastructure heritage preservation that requires special attention from the departments concerned, in order to accurately predict maintenance, reinforcement and planning interventions, which requires effective methods for visualizing and tracking the network. This research aims to integrate techniques of the Geographic Information System (GIS) for modeling, classifying and analyzing the evolution of two parameters: Traffic and pavement deterioration. In this context, a case study examining GIS spatial representation options visualized these two parameters on national, regional and provincial roads in the Berkane province in Morocco based on the results of traffic investigations and visual surveys of pavement deterioration between 2016 and 2022. This study will provide road network managers and decision-makers with the information they need to make the right decisions regarding future maintenance programs.